Model Pembelajaran Kooperatif STAD Untuk Meningkatkan Hasil Belajar Servis Atas Permainan Bolavoli - Budiman Agung Pratama (Journal Coaching Education Sports, 2020)
The purpose of this study was to improve learning outcomes for volleyball service service through the STAD learning model. This research uses the Action Research model of Kemmis & McTaggart with the following stages: Planning, implementation of action, observation, repair or reflection. The subjects in this study were students of class X1 SMA Negeri 1 Kediri with a total of 24 male students and 16 female students, the instrument used in this study was the volleyball service observation sheet. Data on service performance results for volleyball cycle I and cycle II test, the results are determined based on individual completeness, classical completeness. students' average ability . The increase in the percentage of learning completeness from the first cycle to the second cycle was 46.925%. The results of this study can be concluded that the application of the cooperative learning model Student Team Achievement Division (STAD) is effective in improving learning outcomes for volleyball service in class X.1 students of SMA Negeri 1 Kediri